Avoiding failures during building construction using structural fuses as load limiters on temporary shoring structures. (1st February 2020) - Buitrago, Manuel; Sagaseta, Juan; Adam, Jose M.
Highlights: Load limiters (LL) to shoring systems in construction were investigated. FE models were carried out of a RC building with and without LL. Two local failure scenarios were investigated representing accidental events. With LL, the residual damage was reduced due to the activation of more shores. The risk of failure of the temporary structure was mitigated using LL. Abstract: The risk of structural failure of buildings can be significant during construction. Temporary adjustable telescopic steel shores or props are commonly used in building construction. The failure of shores is sudden and therefore structural fuses as load limiters (LL) can be introduced to provide ductility in the temporary member for a specified limit failure load. Previous work by the authors showed that the design of shoring systems can be improved using LL for standard cases of imposed loads applied during construction. This paper extends this work to cases of accidental loading where the shoring system-permanent structure interaction is less known. The main principles of LLs are discussed and implemented in advanced numerical simulations of a real case RC building during construction by means of explicit nonlinear dynamic finite element analyses. Different local failure scenarios were investigated corresponding to cases observed in practice. The comparison of the numerical results obtained with and without LLs demonstrated for the first time the benefits of using LLs in terms of: (a) mitigating the risk of failure of the temporary structure; and (b) reducing permanent damage (cracking and short-term deflections in the slab) affecting the durability and functionality of the building.